Implementasi Model Pembelajaran Kooperatif Contextual Teaching and Learning untuk Meninggkatkan Hasil Belajar Matematika Pokok Bahasan Aritmatika Sosial bagi Siswa SMP Negeri 1 Pemenang - Uswatun Hasanah (Jurnal Paedagogy, 2022)
The purpose of this research is to improve the mathematics learning outcomes of social arithmetic subjects for students through the application of the contextual teaching and learning (CTL) cooperative learning model. The research method used is classroom action research which is carried out in two cycles. The subjects of this study were students of class VII.2 of SMP Negeri 1 Pemenang, totaling 21 students. This research instrument uses observation sheets, documentation, and tests. While the data analysis technique used is quantitative descriptive analysis. The results of this study indicate that student learning outcomes have increased by an average of 9% obtained from the average evaluation of student learning outcomes from the first cycle is 76% then increased in the second cycle to 85%. Based on data analysis during cycles I and II, it can be concluded: (1) The application of the CTL cooperative learning model is the best alternative in learning mathematics, (2) The application of the cooperative model can create participatory and multidirectional learning, (3) Through the application of the CTL cooperative learning model, it can improve student learning outcomes. The results also show changes in the classroom atmosphere that tend to be democratic and changes in teacher attitudes to care more about the classroom atmosphere.